Contextualising CSR in Asia: Corporate Social Responsibility in Asian economies - Sharma, Bindu (Institutional Knowledge at Singapore Management University, 2013)
This publication seeks to present a narrative about the practice of CSR in ten Asian economies – China, India, Indonesia, Japan, Malaysia, Philippines, Singapore, South Korea, Taiwan and Thailand. The aim is to present a uniquely Asian perspective on the CSR story in these countries that will inform CSR practitioners, researchers and interested corporate stakeholders. Drawing on historical and traditional notions of business responsibility and engagement, the research looks at modern day drivers of CSR in these countries such as the government, civil society, globalisation and enlightened self-interest. The research also throws light on other underlying influences and looks at frameworks such as ISO 26000 for Social Responsibility.